Hegel's Time: Between Tragic Action and Modern History. Issue 3 (December 2019) - Pérez, Berta M.
Abstract: This paper offers an alternative perspective to the traditional interpretation of Hegel's philosophical reflection on history, departing from a reinterpretation of Hegel's reading of the tragic action of Antigone in Chapter VI of the Phenomenology of Spirit . The customary interpretation of this text affirms that Hegel shows how the conflict of tragic action finds its truth and its end in the identity of spirit. Tragic conflict is left behind to the same extent that (modern historical) spirit sublates the Greek ethical substance. This way, spirit can guarantee that our historical time is released from the past of the substance, or the spiritual movement of mediation from the immediacy of an 'in-itself'. My reading, by contrast, finds under the tragic conflict of this text of Hegel's nothing but the 'no' of death that negates itself, or a principle that has the form of an original and irreducible conflict. Under this interpretation of Hegelian spirit, it becomes clear that it can neither fail to posit some form of 'in-itself' nor sublate its own tragic nature. This way it is shown that Hegel's reflection on the past does not reassure the superiority of the identity of the (modern) present (as the end of history), but rather illuminates its 'broken' nature. I thus offer an alternative view on Hegel's comprehension of the relation between present and past and between philosophy and time.